Crushing of steel tubes with different infills under partial axial loading. (April 2020) - Ghanbari-Ghazijahani, Tohid; Nabati, Amin; Gorji Azandariani, Mojtaba; Fanaie, Nader
Abstract: Localised/partial loading is seen in many applications in the building and construction industry. This paper aims to study the influence of localised loading in different positions and Loading Coverage Areas (LCAs) for steel columns with concrete and timber infills, and hollow steel tubes. Fifteen tests were carried out in three categories. Structural stability of the specimens was evaluated far into their plastic response up until crushing. The energy absorption of each specimen was quantified and compared with its counterparts of different materials and LCAs. Axial capacity and failure were focused on as well as the strength-to-mass ratio for each specimen. There was a noticeable capacity difference between the side-loaded and mid-loaded specimens of each group indicating the effect of material under loading on the capacity. The side-loaded specimens had a higher interface between the loading element and steel, compared to the mid-loaded specimens. Numerical analysis was also conducted, which yielded a very close consistency of results with the experiments. Graphical abstract: Image 1 Highlights: The side-loaded specimens had a higher interface and capacity compared to the mid-loaded specimens. For partial loading, the material underneath the loading point had a significant effect on the capacity. Having compared all specimens, the concrete-filled tubes experienced higher stability after the yield. The average ductility of timber-filled tubes was higher than hollow sections, while SAE of the hollow sections was higher.